Restorasi dan Perencanaan Struktur Kuda-kuda Istana Bala Gambir Sumbawa - Pratiwi Dian Ilfiani; Tri Satriawansyah; Arbi Batulante; Gita Safitri (Universitas Islam Raden Rahmat, Malang, 2023)
The palace known as Bala Gambir was established in 1936, under the rule of Dewa Masmawa Sultan Kaharuddin III. Only the foundation of Bala Gambir Palace is left as of right now. This study aims to reveal how the Bala Gambir Palace was formed and to determine the safety of the truss structure. The Bala Gambir Palace has a form that resembles a one-story building with a second level. Due to the balcony in front of the palace, which gives the impression that it is a two-story building. A 13.2 meter span easel structure for Bala Gambir Palace was calculated, and the findings showed that the truss framework met the safe limit depending on the size of the wood utilized, which was 8/18 cm. From the calculation, the actual bending stress value is 14.064 MPa < 14.317 which is the corrected flexural strength design value. The gording's total deflection value is 10.47 17.5 mm, which is the permitted deflection limit. Additionally, it is secure from buckling situations with a value of 32.5 < 50 mm.